Extrajudicial Killing By the Rodrigo Duterte Regime in the Philippines From an International Law Perspective - Paputungan, Sarah Nabila (Universitas Negeri Gorontalo, 2024)
This study aims to determine the regulation of narcotics in the Philippines according to the National Police Commission, National headquarters Philippine National police Office of the Chief, PNP About Command Memorandum Circular No.16-2016, and analyze how Access to Justice in the perspective of international law against Crimes Against Humanity by President Rodrigo Duterte. The research method used is a normative legal research method with statutory approaches (Statute Approach) and case approaches (Case Approach). The results of the study show that the Extrajudicial Killing that occurred in the Philippines by the Rodrigo Duterte regime contradicts the provisions of Command Memorandum Circular No. 16-2016 concerning the PNP Anti Illegal Drugs Campaign Plan-Project